When Hattie finds love - Lillard, Amy (Lillard, Amy. Paradise Valley series., 2023)
The Widows Club's most outgoing member, Hattie Schrock, when her cousin bets her she can't help Paradise Valley's most difficult man learn to be happier, tackles the challenge head-on only to discover that Christian Beachy is more complicated-and appealing-than she thought.